학생정신건강사업 현황 및 관련 교육 요구도: 초중고 보건교사와 상담교사 대상 - 진영란; 강미경; 이윤정; Chin, Young Ran; Kang, Mi-Kyung; Yi, Yunjeong (韓國學校保健學會誌, 2018)
Purpose: The leading cause of death among teenagers in Korea is suicide. Also, it is known that mental health of Korean adolescents identified based on the levels of perceived stress or depression is very poor. The purpose of this study was to examine the current status of student mental health programs in Korea and the associated problems and to explore ways to make the programs more effective. Methods: The subjects of the study were a total of 115 school nurses and school counselors in elementary, middle and high schools. The study examined the current status and the associated problems of school mental health programs as well as the needs for teacher training programs related to student mental health. Results: Few mental health programs other than counseling for at-risk students were being carried out. The problems associated with student mental health management were, in terms of management, 'accountability in case of incidents such as student suicide' and 'parents uncooperative in their kid's mental health management (visit to hospital, etc.)' and, in terms of manpower, 'unclear R&R between school nurses and school counselors' and, more fundamentally, 'the lack of human resources.' The needs for teacher training programs related to student mental health were very high and the content required most was 'ways to manage stress of students and teachers themselves,' followed by 'interpersonal conflicts management & conservational skills,' and 'ways to manage student mental illness.' Conclusion: In conclusion, to increase the effectiveness of student mental health programs, we should move on from the current system which focuses only on early discovery and intervention to a more comprehensive system that includes preventive approaches, while having clearer R&R and more workforce dedicated to student mental health programs and attracting more parental cooperation and support.